Ghost hunter - Paver, Michelle (Paver, Michelle. Chronicles of ancient darkness, 2010)
To fulfill his destiny, Torak must defy demons and tokoroths, navigate through the Gorge of the Hidden People, and battle the evil Eagle Owl Mage.